2022
DOI: 10.3390/metabo12050369
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Technique to Simultaneously Characterize Fatty Acid Uptake, Mitochondrial Activity, Vascularity, and Oxygen Saturation for Longitudinal Studies In Vivo

Abstract: Aggressive breast cancer has been shown to shift its metabolism towards increased lipid catabolism as the primary carbon source for oxidative phosphorylation. In this study, we present a technique to longitudinally monitor lipid metabolism and oxidative phosphorylation in pre-clinical tumor models to investigate the metabolic changes with mammary tissue development and characterize metabolic differences between primary murine breast cancer and normal mammary tissue. We used optical spectroscopy to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The present Special Issue contains four reviews [ 1 , 2 , 3 , 4 ] and four research articles [ 5 , 6 , 7 , 8 ] with the original work covering a wide range of methods that can be applied to assess and measure several characteristics of tumours.…”
Section: Imaging and Spectroscopic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present Special Issue contains four reviews [ 1 , 2 , 3 , 4 ] and four research articles [ 5 , 6 , 7 , 8 ] with the original work covering a wide range of methods that can be applied to assess and measure several characteristics of tumours.…”
Section: Imaging and Spectroscopic Methodsmentioning
confidence: 99%
“…Dr Deutsch et al presented a non-invasive method to simultaneously measure exogenous reporters of fatty acid uptake and metabolic membrane potential and endogenous contrast related to haemoglobin concentration and tissue oxygenation [ 5 ]. The authors demonstrated the feasibility of this method by showing that Bodipy FL C16 (lipid phosphorylation surrogate) and TMRE (oxidative phosphorylation surrogate) do not crosstalk chemically, optically or biologically, and that these probes are compatible with an inverse Monte Carlo algorithm to extract tissue optical properties and intrinsic fluorescent signals.…”
Section: Imaging and Spectroscopic Methodsmentioning
confidence: 99%
See 1 more Smart Citation